Development and psychometric evaluation of the Knowledge of Malnutrition – Geriatric (KoM‐G) questionnaire to measure malnutrition knowledge among nursing staff in Austrian nursing homes. Issue 1 (3rd April 2014) - Schönherr, Silvia; Halfens, Ruud J. G.; Lohrmann, Christa
<x xml:space="preserve">Abstract</x> Introduction Malnutrition is an internationally prevalent healthcare phenomenon in nursing home residents entailing serious consequences for those who are affected. Lack of knowledge among nursing staff is often discussed as a reason for deficits in nutritional practice. For this reason, a valid and reliable tool is necessary to assess knowledge of malnutrition (KoM) care. The objective of this study was to develop and psychometrically evaluate a questionnaire aimed at assessing the KoM care among nursing staff in Austrian nursing homes. Methods This study follows a psychometric methodological design. The dimensions and items of the questionnaire were derived from a literature review. The content validity was evaluated using a Delphi technique with eight international experts in the field of malnutrition. Item validity in terms of distribution of response alternatives, item difficulty and discrimination index, construct validity in terms of a comparison between predefined known groups and internal consistency using Kuder–Richardson 20 were analysed in a sample of 1152 registered nurses/nurse aides from 66 Austrian nursing homes. Results The Knowledge of Malnutrition – Geriatric (KoM‐G) questionnaire consists of 20 items with six answer options including 'I don't know' with established content validity. The quality of response alternatives ranged from 0.3 to 96.9%. The item difficulty of the total questionnaire was 59.3% and the discrimination index was 0.37, whereas one item had a discrimination index below 0.20 and was therefore deleted. Significant differences in percentage of correct answers between registered nurses and nurse aides, nursing staff with training in nutrition and without as well as between nursing staff with positive attitudes towards nutritional care and neutral or negative attitudes were found. The Kuder–Richardson 20 was 0.69. Conclusion The KoM‐G shows acceptable psychometric properties covering a wide range of items regarding malnutrition and can be applied in nursing home practice, education and research.